VASP: An autoencoder-based approach for multivariate anomaly detection and robust time series prediction with application in motorsport. (September 2021) - von Schleinitz, Julian; Graf, Michael; Trutschnig, Wolfgang; Schröder, Andreas
Abstract: The aim is to provide a framework for robust time series prediction in the presence of anomalies. The framework is developed based on a data set from motorsport but is not limited to this specific area. In motorsport, the usage of sensors during races is generally restricted. Estimating the outputs of these missing sensors therefore provides an advantage over the competition. Deep learning approaches such as long short-term memory (LSTM) neural networks have proven to be useful for that task, however, their accuracy decreases significantly if anomalies occur in the input signals. To overcome this problem, we propose the variational autoencoder based selective prediction (VASP) framework which combines the tasks of anomaly detection and time series prediction. VASP consists of a variational autoencoder (VAE), an anomaly detector and LSTM predictors. Depending on the anomaly detector, a subset of the inputs may be replaced by the VAE, allowing a more robust prediction. To the best of our knowledge the approach of using a VAE to only selectively replace anomalous input data before prediction has not yet been published. Our contributions are clear implementation guidelines and a comparison to other VAE-based methods and a LSTM approach as baseline. We simulate anomalies with three approaches and show that VASP outperforms other methods by having no trade-off between accuracy and robustness. VASP is as accurate as the baseline for regular data, but for anomalous inputs the error is reduced by 13% to 33% on average and up to 70% in special cases.